Urban areas and isolated remnants of natural habitats: An action proposal for botanical gardens - Pinheiro, Marcelo H. O.; Neto, Luiz C. de Almeida; Monteiro, Reinaldo (Springer, 2006)
The International Union for Conservation of Nature and Natural Resources (IUCN) and the World Wide Fund for Nature (WWF) advocates an increase of the number of botanical gardens throughout the world as one of the measures that can help to preserve the world's biodiversity. To implement this strategy, the present work brings forward a suggestion particularly suited to tropical regions: establishing municipal botanical gardens. It refers to the experience of a newly opened municipal botanical garden in Brazil, comparing its attractive power on visitors to that of other botanical gardens included in the Brazilian network of Botanical Gardens. It also presents considerations on in situ conservation in small remnants and on the importance of urban reserves to preserve the regional biodiversity and spread the conservationist philosophy. The present proposal promotes the participation of local communities making the public opinion more aware and active, besides being able to counterbalance proposals that support protecting the world biodiversity through interventionist actions. It assumes that, through actions planned and coordinated by regional and national botanical garden networks, the measure proposed can mitigate the anthropic actions exerted on important natural reserves all over the world.
Keywords: biodiversity; botanical garden network; environmental education; municipal remnants; urban reserves